2021
DOI: 10.22594/10.22594/dau.20-862.28.03
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effects of Aircraft Engine Upgrades on Operating and Support Costs

Abstract: For fixed wing aircraft within the U.S. Air Force, Operating and Support (O&S) costs encompass a large portion of total life-cycle costs. O&S costs include fuel, maintenance, and engine upgrades. To the authors’ knowledge, no study to date has attempted to empirically quantify the realized effects of new aircraft engines on sustainment costs. Utilizing the Air Force Total Ownership Cost database, they focused on new engines appearing on the C-5s, C-130s, and C-135s. Although narrow in scope, results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They developed cost estimating relationships at the component level for estimating maintenance costs for commercial aircraft. Myers et al (2021) examined the impact of engine upgrades on O&S costs for USAF C-5, C-130, and C-135 aircraft. They found that increased fuel efciency from upgraded engines helped reduce O&S costs.…”
Section: Oands Costs For Aircraftmentioning
confidence: 99%
“…They developed cost estimating relationships at the component level for estimating maintenance costs for commercial aircraft. Myers et al (2021) examined the impact of engine upgrades on O&S costs for USAF C-5, C-130, and C-135 aircraft. They found that increased fuel efciency from upgraded engines helped reduce O&S costs.…”
Section: Oands Costs For Aircraftmentioning
confidence: 99%